Numerical Study on Static and Dynamic Load Response of Temporary Support System for Group Tunnels Excavation - Yu Zeng; Bo Huang; Yu Zou; Yao Bai (Buildings, 2022)
In this study, the static response of the preliminary pilot tunnels excavation to the ground, and the dynamic response of the group cavern system under seismic excitation under the use of the construction of a metro station based on the Pile-Beam-Arch approach are investigated through numerical calculation. The results suggest that the excavation sequences of “top first and then bottom” and “middle first and then both sides” can generate the minimum ground settlement. When the pilot tunnels were excavated, the horizontal PGA (peak ground acceleration) amplification coefficient tends to increase with significant nonlinear characteristics under the excitation of EI Centro wave with a horizontal acceleration of 0.15 g, and the horizontal PGA amplification coefficient reaches the maximum at the ground surface. The effect of horizontal acceleration around the upper pilot tunnels increases. Under the static load, the maximum principal stress of the lining structure after the completion of the pilot tunnels is largely concentrated at the foot of the arch of the pilot tunnel, and the maximum principal stress value is 1.124 MPa. The maximum principal stress is primarily concentrated at the foot of the arch and the foot of the upper and lower guide tunnel under seismic excitation, and the maximum principal stress value is 1.424 MPa. This study reveals that a reasonable excavation sequence can be employed when the pilot tunnels are being excavated to control the settlement. Furthermore, the support of the arch and footing of the pilot tunnels should be enhanced during the seismic design.